Evaluation of a sex-specific difference in lung cancer radiation risk and approaches for improving lung cancer radiation risk projection (with a focus on application to space activities) (National Council on Radiation Protection and Measurements, 2022)
"The study of Japanese atomic-bomb survivors exposed acutely to ionizing radiation in 1945 reported the risk of radiation-related lung cancer to be nearly three times greater for females than for males on a relative scale (similar for both mortality and incidence). The operational model for risk of exposure-induced death currently in use by the National Aeronautics and Space Administration (NASA) relies on data from the Japanese atomic-bomb survivor study. According to the NASA model, radiation-related lung cancer is the largest contributor to fatal cancer risk. The sex-specific difference in lung cancer observed for Japanese atomic-bomb survivors is used in the model, resulting in a higher estimated total cancer mortality risk for female astronauts than for male astronauts for the same level of exposure. NASA requested that the National Council on Radiation Protection and Measurements (NCRP) evaluate the risk of radiation-related lung cancer in populations exposed to chronic (protracted or fractionated) radiation, in order to investigate whether a similar sex- specific difference in lung cancer risk is observed when exposure occurs gradually over years (such as experienced by astronauts during space missions) contrasted with the acute exposure received by the Japanese atomic-bomb survivors"-- Provided by publisher.
Keywords: Astronauts.; Lungs -- radiation effects.; Risk assessment.; Lung Neoplasms.; elektronické knihy; electronic books